Hydrological Impacts of Climate Change in a Well-preserved Upland Watershed - de Moura C.N. (2020)
© 2020, Springer Nature B.V.Much attention has been focused on investigating the effects of climate change on hydrological processes on a regional scale. However, the landscape approach, especially the case of well-preserved upland watersheds needs to be further studied. The Representative Concentration Pathway (RCP) or emission scenarios RCP 4.5 and RCP 8.5 were used to project the impacts of the climate change on the hydrological components of a well-preserved upland landscape with temperate climate, using the Upper Canoas watershed as a case study. The future hydrological projection indicated an increase in the monthly rainfall as well as a shift in the rainiest months from winter to spring. This change resulted in an increase in water balance components. The maximum discharges, as well as the modal discharge (Q50), may increase in the future, and the minimums corresponding to Q95 and Q98 may reduce for both emission scenarios. The results showed that a well-preserved upland watershed in a sub-tropical region might be capable of maintaining water availability at level that is enough for human activities in the future, even with the reduction of minimum permit discharge, which is supported by the increase of maximum and medium monthly discharges and a stable flow-duration curve.